Identification and Mechanism of Echinochloa crus-galli Resistance to Fenoxaprop-p-ethyl with respect to Physiological and Anatomical Differences - Amany Hamza; Aly Derbalah; Mohamed El-Nady (The Scientific World Journal)
Identification and mechanism of Echinochloa crus-galli (L.) resistance to fenoxaprop-p-ethyl via physiological and anatomical differences between susceptible and resistant were investigated. The physiological and anatomical differences that were take into account were growth reduction, chlorophyll content reduction, lamina thickness, and xylem vessel diameter in both susceptible and resistant biotypes of E. crus-galli. The results showed that the growth reduction fifty (GR50) of resistant biotype was 12.07-times higher than that of the susceptible biotype of E. crus-galli treated with fenoxaprop-p-ethyl. The chlorophyll content was highly reduced in the susceptible biotype relative to the resistant one of E. crus-galli treated with fenoxaprop-p-ethyl. An anatomical test showed significant differences in the cytology of susceptible and resistant biotypes of E. crus-galli treated with fenoxaprop-p-ethyl with respect to lamina thickness and xylem vessel diameter. The resistance of E. crus-galli to fenoxaprop-p-ethyl may be due to the faster metabolism of fenoxaprop-p-ethyl below the physiologically active concentration or the insensitivity of its target enzyme (Acetyl-CoA carboxylase).